Perancangan Perangkat Lunak Pembelajaran Mikroprosesor Dengan Menggunakan Metode Computer Assisted Instruction - Berto Nadeak; Sony Bahagia Sinaga (Yayasan Kita Menulis, 2020)
The microprocessor that became the machine for the IBM PC / XT microcomputers and their compatible. This processor is often referred to as simply